Development reading 2 - Buendicho, Floreliza C (Manila, 2010)
This book exposes students to the different methodologies of teaching at different levels in different areas of skills. Based on interactive reading model, the book emphasizes reading to learn. It aims to help readers develop an increasingly complex understanding of the reading process through the application of a series of incremental strategies. The book includes samples of instructional materials and learning activities to enhance student's reading skills
Keywords: Reading Comprehension